2021
DOI: 10.3390/pathogens10070833
|View full text |Cite
|
Sign up to set email alerts
|

Pet Pyometra: Correlating Bacteria Pathogenicity to Endometrial Histological Changes

Abstract: Pyometra is a life-threatening infectious disease that frequently affects bitches and queens. Although histopathological patterns of pyometra have been extensively explored, the microbiological aspects, such as bacteria pathogenicity, have not been correlated to microscopy endometrial lesions so far. In this study, these two pathological aspects of pyometra were analysed and correlated. Uterus fragments and intrauterine content samples were collected from pets diagnosed with pyometra (30) and submitted to hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 23 publications
2
18
2
2
Order By: Relevance
“…In the present study, phylogroup B2 was the most frequent in the uterine contents of bitches, with clinical cases of pyometra caused by E. coli ( Figure 1 ), corresponding to 85% of the isolates. This frequency is similar to that found in previous studies on pyometra, suggesting a high capacity of phylogroup B2 strains to colonize the canine uterus [ 7 , 11 , 31 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the present study, phylogroup B2 was the most frequent in the uterine contents of bitches, with clinical cases of pyometra caused by E. coli ( Figure 1 ), corresponding to 85% of the isolates. This frequency is similar to that found in previous studies on pyometra, suggesting a high capacity of phylogroup B2 strains to colonize the canine uterus [ 7 , 11 , 31 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although the pathogenesis of pyometra is poorly understood, previous studies have suggested that the intestine is the main source of E. coli strains that ascend into the uterus [ 1 , 2 , 7 ]. This study reinforces this hypothesis, as bitches with E. coli pyometra were more likely to harbor E. coli strains from phylogroup B2 in the rectal swab when compared to the group of bitches without E. coli pyometra.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations